2021
DOI: 10.1111/tid.13757
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term liver transplant outcomes from SARS‐CoV‐2 lower respiratory tract NAT positive donors

Abstract: On April 2021, the United States Organ Procurement and Transplantation Executive Committee approved the "lower respiratory SARS-CoV-2 testing for lung donors" emergency policy upon recommendation from the Ad Hoc Disease Transmission Advisory Committee. This policy requires that all lung donors be tested for SARS-CoV-2 in a lower respiratory specimen by nucleic acid test (NAT) and that the results be available before the lungs are transplanted. The overarching goal of the emergency policy was to minimize the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 11 publications
3
37
0
2
Order By: Relevance
“…These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs. 7 , 8 , 9 , 10 , 11 , 13 , 20 , 21 In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors. Similarly for liver and transplant recipients, both general characteristics of recipients and 6‐month graft survival were similar by SARS‐CoV‐2 status donors.…”
Section: Discussionmentioning
confidence: 55%
“…These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs. 7 , 8 , 9 , 10 , 11 , 13 , 20 , 21 In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors. Similarly for liver and transplant recipients, both general characteristics of recipients and 6‐month graft survival were similar by SARS‐CoV‐2 status donors.…”
Section: Discussionmentioning
confidence: 55%
“… 22 Since then, several transplants have been performed, most of which were liver, kidney, and (to a lesser extent) heart. To date, no cases of SARS-CoV-2 transmission after non-lung transplant have been reported 16 23 6 24 25 7 . 21…”
Section: The Use Of Organs From Deceased Donors With Active Sars-cov-...mentioning
confidence: 99%
“…As of today, in our national experience with 71 organ transplants performed from donors with active SARS-CoV-2 infection and on the basis of current literature with overall 455 non-lung organs (278 kidneys, 125 livers, 41 hearts, and 11 pancreas) transplanted from donors with a positive lower respiratory tract SARS-CoV-2 test, no recipients acquired COVID-19 infection through non-lung transplantation. In contrast there have been three unexpected donor derived transmissions to lung recipients, because the donor tested negative for SARS-CoV-2 in an upper respiratory tract specimen but retrospectively tested positive in a LRT specimen 26 16 23 6 24 25 7 . 21…”
Section: The Use Of Organs From Deceased Donors With Active Sars-cov-...mentioning
confidence: 99%
“…To date, there are no reports on the use of SARS‐CoV‐2 LRT NAT positive donors for kidney transplantation, and limited case reports have evaluated the safety of using liver allografts from these donors. 4 , 5 The weight of the evidence including the absence of proven cases of SARS‐CoV‐2 transmission from positive non‐lung donors suggests that the risk of transmission is low. 1 , 4 , 5 , 6 From May 27 through November 30, 2021, 178 non‐lung organs were transplanted from donors with a positive lower respiratory tract SARS‐CoV‐2 test.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 The weight of the evidence including the absence of proven cases of SARS‐CoV‐2 transmission from positive non‐lung donors suggests that the risk of transmission is low. 1 , 4 , 5 , 6 From May 27 through November 30, 2021, 178 non‐lung organs were transplanted from donors with a positive lower respiratory tract SARS‐CoV‐2 test. 6 The safety of using organs in this scenario remains unknown.…”
Section: Introductionmentioning
confidence: 99%